(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The kedu-Parakan arterial road is a national road that has the second-highest number of accidents in Temanggung Regency. Traffic accident data in 2014-2018 as many as 80 times. The purpose of the study is to identify the causative factors of the accident and evaluate the suitability and analysis of Kedu-Parakan Road as a safe road to improve it. Data analysis uses correlation with SPSS Program and collision diagram. The main cause of the accident (75%) is human, and the type of collision that often occurs is front-to-front collisions (42.5%), as well as the type of vehicle often involved is motorcycles (65.2%). The accident time often occurs at 06.00 WIB-12.00 WIB (45%), wherein this section there are 3 blackspots, namely: STA 01+050-STA 01+350 (4 events), STA.03+900-STA 04+300 (5 events), and STA 07+500-STA 07+800 (4 events). Recommended types of person crossings suitable for STA 01+050-STA 01+350 and STA 07+500-STA 07+800 with PV2 values of 3 x 108 in the form of zebra cross, renewal of signs and markings, and the creation of a single School Safe Zone (ZOSS) at STA 03+900-STA 04+300.